(untitled) (Al-Academy, 2017)
Means the current research study in the direction iconic structures plates Ottoman calligraphers , as they took turn in this area and because it excelled in the form of a strong incentive and motivation to seek calligraphers in this direction so as to simulate the skill of the artist and parallel to the side of his creativity as well.And iconography , RECEIVED of objective vision and aesthetic and semantic in the output of compositions written according to the specific significance and this has a clear impact on the propensity to develop technical and aesthetic and expressive in the output of the structure of synthetic iconography is limited by rules or building in the form of public panel linear . And that all forms , whether animal , human figures , floral or geometric shapes , architectural , is mimic nature.The principle of iconography . Is a struggle structural creates the idea of conceptual literary art evolve through that conflict , they have a role to my readers Alami employed in posters and advertisements through the implementation of compositions iconic significance in accordance with the content of the text , where the text reads through the output format instead of text , linguistically , and this recipe The functional principle of the reductionist iconography , as well as the transfer of the Arab character of blogging to stage what it now has connotations of configurations consistent with the content of the texts executed this is the advanced stage of Arabic calligraphy